Anti-carbamylated protein antibodies in rheumatoid arthritis patients are reactive to specific epitopes of the human fibrinogen β-chain - Corsiero, Elisa; Bombardieri, Michele; Pitzalis, Costantino (Journal of Laboratory and Precision Medicine, 2017)
In this issue of Arthritis & Rheumatology, Jones et al. aim to identify the presence of immunodominant epitope(s) within human fibrinogen in regards to the anti-carbamylated protein antibodies (ACarPA) reactivity in rheumatoid arthritis (RA) patient sera.